Role of the nuclear factor kappa Beta ligand (RANKL) in osteoarthritis and oseteoclastogenesis in thoroughbred horses. Use of anti-inflammatory drugs. - De Negri, Luis (2021)
Osteoarthritis (OA) is one of the main conditions that affects the performance of sports horses. Early diagnosis of the disease is relevant in its clinical and therapeutic management. The evidence shows that this process has a clear relationship between osteoclasts and immune cells sharing molecules such as cytokines, receptors, signaling molecules and transcription factors that influence each other where they play a crucial role in both pathological and physiological bone resorption. The role of the nuclear receptor activator ligand-KB (RANKL) is described as one of the most relevant cytokines that induce osteoclastogenesis.